OBYEKTIVITAS SURAT KABAR REGIONAL PADA PEMBERITAAN CAGUB DAN CAWAGUB PILKADA LAMPUNG 2014 - Wulan Suciska; Andi Windah; Toni Wijaya (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2015)
This study examines the objectivity of daily newspapers (SKH) on the news about Governor and Vice Governor Candidate in Lampung Province General Elections on 2014. Newspaper as a form of mass media used to interpret and reassemble the complex facts of reality into a meaningful story which can be understood by audiences. One of the main events that have been constructed in advance is a political event. Political coverage has dimensions of public opinion formation (public opinion) because it could affect the political achievement of political actors. The formation of public opinion in Lampung Provincial General Election also takes place during the campaign before the vote (1-7 November 2014). The news was reported by Lampung Post Daily Newspaper, Tribun Lampung Daily Newspaper and Radar Lampung Daily Newspaper. This study uses a quantitative approach with content analysis method (content analysis). As a result, the Tribune Lampung Daily Newspaper has higher values in reporting the news’ factuality and impartiality principles. This difference is attributed to the editorial policy of the media and also the object influencingfactor such as the object’s strategic position and financial strength.